Physiology of Pulmonary Circulation & Related Structures - Algul, Sermin; Ozcelik, Oguz (Nobel Tip Kitabevleri, 2024)
The pulmonary circulation, which includes the movement of blood from the heart to the lungs and back, facilitates gas exchange and serves several other functions. It differs from systemic circulation but is crucial for maintaining homeostasis. Pulmonary vessels protect against thrombi and emboli, metabolize vasoactive hormones, and act as a blood reservoir. Hemodynamically, pulmonary circulation is characterized by high flow, low pressure, and low resistance. Pulmonary vascular resistance adjusts to changes in cardiac output and lung volume, impacting gas exchange efficiency. Hypoxia can induce pulmonary vasoconstriction, affecting blood flow distribution. In summary, pulmonary circulation plays a vital role in gas exchange and overall circulatory function.The exchange of fluids in pulmonary capillaries is governed by factors such as hydrostatic and colloid osmotic pressures, similar to systemic circulation. Additionally, alveolar surface tension and pressure play crucial roles in fluid movement. Pulmonary edema, characterized by fluid accumulation in the lungs, can result from various factors including increased capillary pressure, permeability, or surface tension, as well as decreased plasma osmotic pressure. Lymphatic drainage helps remove excess fluid from the lungs. Blood flow in the lungs varies due to gravity, with greater flow in the lower regions. Ventilation-perfusion imbalances occur, influencing gas exchange efficiency. Regional disparities in ventilation-perfusion ratios are associated with diseases affecting different lung areas, such as tuberculosis being more common in the upper parts due to favorable oxygen levels.Shunts and Venous Mixing: In the lungs, venous admixture, which is a mixture of oxygenated and deoxygenated blood, occurs due to shunts and a low ventilation-perfusion (VA/Q) ratio. Anatomical shunts occur through defects in the heart or pulmonary vessels, while a low VA/Q ratio results from inadequate oxygenation despite blood flow. Approximately 50% of venous admixture originates from anatomical shunts, while the rest is due to a low VA/Q ratio, particularly at the lung base. Both shunts and a low VA/Q ratio contribute to disruptions in gas exchange.Bronchial Circulation: Bronchial circulation supplies blood to the walls of conducting airways but not to the terminal respiratory units. It consists of two pathways for venous return: bronchial veins and pulmonary veins. Bronchial blood flow accounts for 1-2% of cardiac output and can increase in inflammatory conditions. Neovascularization capacity allows bronchial circulation to provide collateral circulation in lung parenchyma, crucial in situations where pulmonary circulation is compromised.